Fana’ dalam Pandangan Ulama Sufi: Tinjauan terhadap Pemikiran Sufi Sheikh Hamzah Fansuri - Jerri Gunandar (SHIBGHAH: Journal of Muslim Societies, 2021)
AbstractFana’ is term for annihilation of the self-appreciation, a concept highlighted in Sufism represents the vanishing of the human wicked attributes that is embellished by various demands of evil desires. On the other hands, Fana’ is also refers to the only concentration of the memory in appreciation of the perfection and the glory of Allah SWT. This is because fana' is a high level stage of consciousness and a precise focus attentions only on Allah SWT to the stage that other things to be blunt as if lost from seeker’s memory. Nevertheless, in the discourse of Islamic thoughts, many misunderstandings and misappropriation are correlated to the concept of fana’ that occurs in Sufis path. Therefore, this article efforts to high spot the concept of fana’ conferring to Sheikh Hamzah Fansuri (d.1630) through his work to scrutinize the extent to which the concept of fana’ posed by him in line with other well-known Nusantara Sufi figures. This study uses the content analysis method by referring to the work of Sheikh Hamzah Fansuri sufi entitled "Asrar Al-‘Arifin". The study found that the term of fana' presented by Sheikh Hamzah Fansuri was in line with the meaning of fana' which was emphasized by the previous Nusantara Sufi figures such as Sayyid Abdul Rahman (d.1917), Sheikh Abdul Samad al-Falimbani (d.1788) and other ancient Sufis figures. However, the use of the term is somewhat different in explaining the fana's meaning since Sheikh Daud al-Fatani in his work emphases more on the aspect of the existence stage which he labeled as the seventh stages. The study concludes that the concept of fana' posed by the figure was an essential bridge in understanding the concept of fanā' adopted by the practitioners of Sufis path among society nowadays